Advancing Sustainability through Energy Innovation and Climate Action: Insights from ETUT - Gurbanmyrat Mezilov; Mekan Toyjanov; Mukam Ekayev; Dovlet Annamuradov; Mavluda Babayeva; Yslam Orazov (Journal of Sustainability Perspectives, 2024)
This study explores the potential of sustainable energy solutions to address global energy challenges and mitigate climate change. Oguz Han Engineering and Technology University (ETUT) serves as a case study, displaying its innovative approaches to energy efficiency, waste management, and renewable energy production. The university's implementation of energy-saving devices, smart building automation systems, and LED lighting demonstrates a commitment to reducing carbon emissions and promoting sustainable practices. Additionally, the study investigates the conversion of plastic waste into liquid fuel and the production of bioethanol from cotton stalks as potential solutions for waste management and renewable energy generation. Further, the research explores the deposition of thin film bismuth vanadium tetraoxide for hydrogen production, highlighting its potential as a clean energy source. Overall, this study emphasizes the importance of sustainable energy solutions and the role of academic institutions in driving innovation and promoting a greener future.